Case Report: Arthroscopic treatment of calcific periarthritis of the knee in the lateral and medial collateral ligaments - Liu, Changli; Yu, Guosheng; Zhao, Xiuquan; Hu, Yanzhao (Frontiers in Surgery, 2025)
ObjectiveCalcific periarthritis, a well-recognized pathological condition of the shoulder joint, also represents an uncommon etiology of severe knee pain. Here, we present a case report of a patient with calcifications concurrently affecting both the lateral collateral ligament (LCL) and medial collateral ligament (MCL).Case descriptionThe 62-year-old woman presented with severe lateral knee pain and restricted range of motion in her right knee. The knee exhibited marked tenderness in the posterolateral region and slight swelling, and maintained ligamentous stability. X-ray imaging of the knee revealed well-defined calcific deposits bilaterally on the femoral condyles. MRI findings indicated hypointense signal areas in close proximity to the insertions of the LCL and MCL. Laboratory test results were within normal limits. A preliminary diagnosis of calcific periarthritis was established based on comprehensive clinical assessments. Given the ineffectiveness of conservative interventions and at the patient's strong request, arthroscopic surgery was performed specifically targeting the calcific deposition in the LCL.ResultsThe patient experienced immediate relief of symptoms following the operation. Intraoperative biopsy validated the initial diagnosis. During the 2-year follow-up period, the patient remained pain-free, and radiographic assessment indicated asymptomatic dissolution of the calcific deposition in the MCL.ConclusionThis study represents the first documentation of calcifications affecting both the LCL and MCL simultaneously. The progression of MCL calcifications demonstrated the potential for asymptomatic presentation from onset to resolution. In cases where conservative management fails to address symptomatic calcific disease of the LCL, arthroscopic surgery may be warranted.